Cardiac magnetic resonance findings in patients recovered from COVID-19: Initial experiences in elite athletes - Vago, H.; Szabo, L.; Dohy, Z.; Merkely, B. (JACC: Cardiovascular Imaging, 2020)
A new study by Puntmann et al. (1) investigating an unselected group of 100 middle-aged patients who had recently recovered from coronavirus disease 2019 (COVID-19) without cardiac symptoms, suggests that an overwhelming 78% of the cases had cardiovascular involvement detectable by cardiovascular magnetic resonance (CMR) imaging. However, it is unknown if there is a cardiac involvement in otherwise healthy young patients after their recovery from COVID-19, especially in elite athletes who gradually return to vigorous exercise after the infection. Our aim was to describe the CMR results of elite athletes recently recovered from COVID-19 with mild to moderate symptoms to provide further insight into this currently very relevant topic